1978
DOI: 10.3171/jns.1978.48.2.0169
|View full text |Cite
|
Sign up to set email alerts
|

Mannitol dose requirements in brain-injured patients

Abstract: There is little information as to the optimal use of mannitol. To determine the dose-response relationship, the osmotic gradient required, and the time course of intracranial pressure (ICP) reduction produced by mannitol, eight patients with acute head injury were studied in whom ICP was monitored with a ventriculostomy and found to be elevated. Ventilation was controlled to a pCO2 of 25 +/- 3 mm Hg and all were paralyzed with Pavulon. None had received barbiturates. Before mannitol administration the intracra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(64 citation statements)
references
References 6 publications
2
61
0
1
Order By: Relevance
“…10,11,29,35 Mannitol reduces ICP and mortality rates after head injury and is superior to pentobarbital in reducing the occurrence and severity of ICP elevations. 30,45,47 However, hypertonic saline (HTS) has increasing pilot data supporting its efficacy. 1,17,20,21,25,48,51 Recent meta-analyses of observational studies comparing mannitol and HTS in the treatment of raised ICP support HTS as a superior agent for lowering ICP.…”
mentioning
confidence: 99%
“…10,11,29,35 Mannitol reduces ICP and mortality rates after head injury and is superior to pentobarbital in reducing the occurrence and severity of ICP elevations. 30,45,47 However, hypertonic saline (HTS) has increasing pilot data supporting its efficacy. 1,17,20,21,25,48,51 Recent meta-analyses of observational studies comparing mannitol and HTS in the treatment of raised ICP support HTS as a superior agent for lowering ICP.…”
mentioning
confidence: 99%
“…Also, Marshall et al have suggested that a mannitol bolus of 0.25g/kg reduces ICP as much as larger doses of mannitol. 27 Based on the results reported by Marshall et al and those of the present study, a mannitol bolus of 0.25 g/kg is allowable a maximum of 6 times per day. This management is used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…If hyperventilation does not control the ICP, mannitol must be administered in a bolus at a dose of 0.25 g/kg. Administering it in infusion or at higher doses do not improve the result [135]. Osmolarity and intravascular volume status must be monitored, because hyperosmolarity or hypovolemia may occur and negatively affect the prognosis.…”
Section: Initial Neurologic Evaluation Of the Trauma Patientmentioning
confidence: 99%